Investigation of the use of ISO 16251-1 for the obtaining of acoustic insulation on floating floor. Issue 2 (June 2022) - Alves Nogueira Braga Neto, Gerardo Braga; Soares Quixaba, Gabriel; De Oliveira Bezerra, Jeferson; De Souza Custódio Filho, Sérgio; de Melo, Gustavo da Silva Vieira; Mesquita, Alexandre Luiz Amarante
ISO 16251-1 standard describes an alternative method for the experimental obtaining of acoustic parameters reduction of the impact sound pressure level ( ΔL ) and weighted reduction of the impact sound pressure level ( ΔLw ) for soft floor coverings through vibration measurements on a small floor mock-up. The application of the methodology to floating floor systems is of great interest, since, compared to the conventional method (ISO 10140-3), it is less costly and would require smaller specimens. However, previous studies have revealed an influence of the modal behavior of the slab on the sound insulation in the frequency range, causing the ΔL curves to show abrupt oscillations (peaks and valleys), thus deviating from the reliable insulation values and decreasing their accuracy. This study proposes the use of ISO 16251-1 for the evaluation of floating floor systems investigating the main factors that influence the accuracy of laboratory tests and the performance of the devices, namely dynamic stiffness of the resilient layer, total loss factor, and dimensions in the floating slab area. The results of ΔL and ΔLw obtained according to ISO 16251-1 were compared to those of two analytical models and the conventional method for 17 samples of floating mortar screeds of 0.96 and 0.36 m 2 areas, 10.8–340.6 MN m −3 dynamic stiffness, and 0.04–0.39 total loss factor. The 0.96 m 2 samples showed less abrupt oscillations in the ΔL curves than those of 0.36 m 2, and the oscillations recorded for resilient layers of above 68.4 MN m −3 stiffness were minimal when the larger floating slab was used.